The eagle and the rose : a remarkable true story - Altea, Rosemary (New York : Warner Books, 1995)
The life of an English clairvoyant and medium. Altea describes the hardship of growing up in an abusive family, forced to conceal her psychic abilities. As an adult, Altea is befriended by a healer, who helps her develop her psychic gifts, and by Grey Eagle, a Native American spirit guide.
Keywords: Altea, Rosemary; Women mediums -- Biography